Tracking the rapid loss of tidal wetlands in the Yellow Sea. Issue 5 (8th May 2014) - Murray, Nicholas J; Clemens, Robert S; Phinn, Stuart R; Possingham, Hugh P; Fuller, Richard A
Abstract : In the Yellow Sea region of East Asia, tidal wetlands are the frontline ecosystem protecting a coastal population of more than 60 million people from storms and sea‐level rise. However, unprecedented coastal development has led to growing concern about the status of these ecosystems. We developed a remote‐sensing method to assess change over ~4000 km of the Yellow Sea coastline and discovered extensive losses of the region's principal coastal ecosystem – tidal flats – associated with urban, industrial, and agricultural land reclamations. Our analysis revealed that 28% of tidal flats existing in the 1980s had disappeared by the late 2000s (1.2% annually). Moreover, reference to historical maps suggests that up to 65% of tidal flats were lost over the past five decades. With the region forecast to be a global hotspot of urban expansion, development of the Yellow Sea coastline should pursue a course that minimizes the loss of remaining coastal ecosystems.